THE CORRELATION BETWEEN EXTRINSIC MOTIVATION AND STUDENTS’ ACADEMIC ACHIEVEMENT IN STUDYING ENGLISH - Fitrianti, Annisa (Universitas Mahaputra Muhammad Yamin, 2024)
This study aimed to investigate the correlation between extrinsic motivation and academic achievement among first-year students studying English at MAS TI Kumpulan during the 2021/2022 academic year. This study revealed several issues affecting students’ motivation in learning English. Specifically, many students lacked interest in studying English, experienced a lack of motivation from teachers, but received a reward at the end of the semester for the highest score. Additionally, a significant number of students failed to complete homework due to inadequate parental support. Furthermore, students found English to be a challenging subject because of a lack of peer support. The study comprised 65 students, with a sample size of 24, selected using purposive sampling. Data were collected using questionnaires and documentation. The coefficient of correlation was determined to be -0.114, indicating no significant relationship between extrinsic motivation and academic achievement in English studies among the students. In other words, according to hypothesis testing, the t-score was -0.114 while the t-table was 0.432. This indicates that the t-score was lower than the t-table. As a result, Ha was rejected and Ho was accepted, indicating that there was no significant correlation between students' extrinsic motivation and their academic achievement in the study of English.